The implementation of the antitrust damages directive in Slovenia: tensions with the (lurking) preventive character of liability in damages? - Weingerl, Petra (LeXonomica, 2021)
In December 2016, Member States need to implement the Antitrust Damages Directive. The Directive adopts the full compensation principle and expressly prohibits overcompensation. I will embark on an enquiry whether such an approach departs from the Slovene general regime of civil liability, in particular liability in damages. At face value, one might argue that the Slovene civil liability regime prohibits non- compensatory rationales for awarding damages. This article challenges this perception. It argues that there is a space for interpreting the rationale for damages in the Slovene private law, when this is justified with dissuasiveness and sufficient reasons are given, as well as embracing non- compensatory considerations, prevention and deterrence in particular. Regrettably, the judiciary does not necessarily keep in step with such an interpretation. However, there are tendencies in the legal scholarship to change the established case law. In this setting, the special liability regime based on the Directive, which prohibits overcompensation, can be seen as an exception to the general regime for damages awards in certain contexts. This approach is contrasted with damages awards regime in the labour law context, which is also based on the EU regulation. In this context, the Slovene legislator expressly embraced prevention and deterrence as rationales for the award of damages. Thus, legislation which is based on or influenced by EU law can lead to different outcomes in practice. It can either reinforce preventive tendencies of the general regime of civil liability or, as it is seen in the competition law context, undermine them. Nevertheless, the (proposed) Slovene implementing legislation opts for a solution that accommodates both the Antitrust Damages Directive and the general regime of civil liability.
Keywords: Antitrust Damages Directive; civil liability; damages; full compensation; prevention; deterrence